Correlation Between Physical Education Achievement, Basic Motor Skills, and Students' Interest in Selected Sports Disciplines - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul (Sains Global Institut, Indonesia, 2024)
This study examined the correlation between Physical Education (PE) achievement, basic motor skills, and students’ interest in selected sports disciplines among students at SMP Negeri 29 Makassar. A quantitative correlational design was employed involving 120 students from grades VII and VIII, selected through stratified random sampling. Data were collected using standardized motor skill tests (TGMD-2), interest questionnaires, and official PE grades from the school’s records. Descriptive statistics showed the mean PE achievement score was 78.5 (SD = 8.3), basic motor skills score averaged 72.4 (SD = 7.5), and sports interest score had a mean of 3.9 on a 5-point Likert scale (SD = 0.6). Normality tests confirmed data distribution was suitable for parametric analysis. Pearson correlation analysis revealed a strong positive correlation between PE achievement and basic motor skills (r = 0.68, p < 0.001), a moderate positive correlation between PE achievement and sports interest (r = 0.52, p = 0.004), and a weak but significant correlation between motor skills and sports interest (r = 0.33, p = 0.023). These findings suggest that motor skill competence and student interest in sports significantly influence PE academic outcomes. The study emphasizes the need for educators to focus on improving motor skills while fostering students’ motivation and engagement in sports activities. Future research should explore longitudinal effects and interventions aimed at enhancing both motor proficiency and sports interest.